Factors before enrolment are associated with being removed from a Pharmacy-only Refill Programme at a large urban HIV/AIDS clinic, Uganda. (February 2014) - Nakiwogga-Muwanga, A; Katabira, E; Kiragga, A; Kambugu, A; Nakibuuka-Lubwama, E; Manabe, YC; Alamo, ST; Colebunders, R
A Pharmacy-only Refill Programme (PRP) a type of task shifting in which stable HIV-positive patients are managed through pharmacy-only visits instead of physician visits. We performed a study to identify factors for being removed from the PRP in order to establish better referral criteria. The study was performed at the Infectious Disease Clinic (IDC) in Kampala, Uganda. We selected a random sample of 588 patients from 2431 patients on antiretroviral therapy referred to the PRP at least 12 months before commencement of the PRP evaluation. We compared the characteristics of patients who during 12 months of follow-up were removed from the PRP with those who continued to be followed up. Data were abstracted from the IDC data base, the pharmacy register and the patient clinical notes. Of 588 patients, 106 (18%) were removed from the PRP. In multivariate analysis, less than 100% self-reported adherence to antiretroviral therapy, missing at least one scheduled appointment in the six months before referral to the PRP and being on a lopinavir/ritonavir-containing regimen were independently associated with being removed from the PRP. Criteria for referring patients to a PRP should focus on antiretroviral therapy adherence and appointment keeping. Patients on a lopinavir/ritonavir-containing regimen should not be targeted for a PRP. On the other hand a PRP is an efficient strategy that targets stable adherent patients in clinics with high patient load.